Investigation of the biological diversity of Trichoptera larvae in the streams of the Kastamonu (Cide)-Sinop (Ayancık) coastal region of Türkiye - Özalp Yasemin; Küçükbasmacı İbrahim (National Library of Serbia, 2023)
This study was carried out to determine the biodiversity and densities of Trichoptera larvae at stations in the Kastamonu (Cide)-Sinop (Ayanc?k) coastal region. Benthic macroinvertebrate samples were collected from each of the 19 stations using the kick-net sampling method with a D-frame net (500-?m mesh). Using the data from collected Trichoptera larvae, the similarity, diversity, dominance and population density relationships among habitats were measured. According to the calculated Shannon-Wiener and Simpson diversity index results, the station with the highest Trichoptera diversity was determined at S2, and the station with the least diversity was S14. Similar results were obtained for the calculated population density values. Station S2 was the most balanced station in population density. Thus, biodiversity was directly related to habitat structure, anthropogenic impact and geographical conditions, and environmental factors suppress biological species diversity. It was concluded that species diversity is greater in undestroyed habitats and less in heavily destroyed habitats. In addition, the species that dominate in biodiversity similarity rates prefer their habitat.
Keywords: kastamonu; sinop; QH301-705.5; Biology (General); trichoptera; biodiversity; 14. Life underwater; 15. Life on land